Analisis Kriminologi Maraknya Tawuran Gangster oleh Anak di Era Digital - Bayu Rizki Yoga Pratomo; Rasdi Rasdi (Annual Review of Legal Studies, 2025)
The phenomenon of inter-gang brawls among teenagers, particularly those involving children in Indonesia, has become a complex and serious social issue. This research provides an in-depth criminological analysis of the prevalence of these brawls, focusing on the digital era's role in shaping and accelerating the dynamics of this deviant behavior. The study identifies both internal and external causal factors. Internally, involved adolescents often experience an identity crisis, possess weak self-control, and struggle with environmental adjustment. Their inability to manage emotions and seek positive recognition pushes them to find outlets in deviant groups. Externally, unfavorable family environments and the influence of deviant peer groups are significant contributing factors. What distinguishes this modern phenomenon is the catalytic role of digital technology, especially social media. Platforms like Instagram and TikTok have become primary arenas for provocation, challenges, and coordination of brawls, even enabling live broadcasts that can influence other adolescents to participate. The lack of parental supervision over children's social media use exacerbates these negative impacts. To address this, a comprehensive approach is necessary, encompassing pre-emptive (early prevention), preventive (ongoing prevention), and repressive (law enforcement with rehabilitation) efforts. This approach involves families, schools, communities, and law enforcement agencies, with an emphasis on restorative justice for children in conflict with the law.